Drug-induced sleep endoscopy: from obscure technique to diagnostic tool for assessment of obstructive sleep apnea for surgical interventions. Issue 1 (February 2018) - Atkins, Joshua H.; Mandel, Jeff E.
Abstract : Purpose of review: Provide a practical update on drug-induced sleep endoscopy (DISE) for anesthesia providers, which can also serve as a reference for those preparing to establish a DISE program. Recent findings: New developments in surgical approaches to OSA and the growing global incidence of the condition have stimulated increased interest and demand for drug-induced sleep endoscopy. New techniques include transoral robotic surgery and hypoglossal nerve stimulation. Recent DISE literature has sought to address numerous debates including relevance of DISE findings to those during physiologic sleep and the most appropriate depth and type of sedation for DISE. Propofol and dexmedetomidine have supplanted midazolam as the drugs of choice for DISE. Techniques based on pharmacokinetic models of propofol are superior to empiric dosing with regard to risk of respiratory compromise and the reliability of dexmedetomidine to achieve adequate conditions for a complete DISE exam is questionable. Summary: The role of DISE in surgical evaluation and planning for treatment of OSA continues to develop. Numerous questions as to the optimal anesthetic approach remain unanswered. Multicenter studies that employ a standardized approach using EEG assessment, pharmacokinetic–pharmacodynamic modelling, and objectively defined clinical endpoints will be helpful. There may be benefit to undertaking DISE studies in non-OSA patients.